IMPROVING STUDENTS’ ACHIEVEMENT IN READING DESCRIPTIVE TEXT THROUGH ACCELERATED LEARNING - Nur Asiah Manik and Bachtiar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This research concerns on improving students’ achievement in reading descriptive text through accelerated learning.  The objective was to find out the improvement of students’ achievement in reading descriptive text. This research was conducted by using action research method. The subject of the research was VIII-2 students of SMP Taman Harapan Medan. The numbers of students were thirty students. They were taught reading descriptive text through accelerated learning. The instruments used were reading descriptive text test, diary notes, interview sheets, and observation sheets. In analyzing data, the mean of students’ score for the first competency test was 49,67, for the second competency test was 68,67 and for the third competency test was 82,6 and the total percentage of improvement from the first competency test to the third competency test was 66,6%. The conclusion is that through accelerated learning can improve the students’ reading achievement in descriptive text. It is suggested that teachers should apply accelerated learning as one of strategy to improve students’ reading achievement in descriptive text.